No efficacy of biofield therapy in the treatment of warts of the hands and feet in adults: a randomized controlled trial. (4th April 2021) - Gaillard, C.; Allain, L.; Rouillon, C.; Desgue, Y.; Brucato, S.; Peyro‐Saint‐Paul, L.; Dompmartin, A.
Summary: Although biofield therapy is unexplained by scientific evidence, it has been practised for many years in numerous cultures for a variety of medical conditions. This study aimed to determine whether one session of biofield therapy with an experienced practitioner could treat warts on the hands and feet in adults. A single‐blind, assessor‐blind, placebo‐controlled, randomized trial was performed between April 2016 and November 2018. The enrolled participants had at least one wart on the hand or foot that had been present for at least 90 days and they were not using any other therapy for the wart. The primary outcome of this trial was the disappearance of the original wart 3 weeks after session of proximal nontouch biofield therapy vs. a sham session. No original wart had disappeared 3 weeks after intervention (0/64), which made the study impossible to conclude on the primary objective. There were no significant differences between the two groups concerning wart disappearance 3 weeks ( P  = 0.49) or 6 weeks ( P  = 0.40) after the intervention. Reduction in wart size at Week 3 tended towards a better result for biofield therapy but this was not significant ( P  = 0.27). No related adverse effects were observed. The major limitation of this trial was the short follow‐up time for measurement of clinical outcome, which did not allow verification of the hypothesis. However, this study shows that 3 weeks after a session of proximal nontouch biofield therapy is an insufficient length of time to assess biofield therapy in comparison with a sham session. Based on this study, biofield therapy cannot be recommended to treat warts within 3 weeks.